SURVEI TINGKAT PEMAHAMAN PEMAIN SEPAKBOLA TERHADAP LAWS OF THE GAME 2010/2011 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Formulation of the problem in this research is how the level of understanding of football players aged 13-15against football rules (laws of the game) 2010/2011 on SSB Se-Waterford County 2013. The purpose of thisstudy was to determine the level of understanding of football players aged 13-15 against the football rules (lawsof the game) 2010/2011 on SSB Se-Waterford County. The method used in this study is a survey. The subjectswere 13-15 years old soccer player in SSB Se-Waterford County in 2013. In determining the subject of thesurvey research was conducted with a total sampling technique. The data was collected using the methods ofdocumentation, observation and questionnaire or questionnaires. Analysis using quantitative descriptivepercentages. Based on the descriptive analysis of percentages, the results showed that soccer players aged 13-15years in SSB Se-Waterford County has a good understanding of football rules (laws of the game) 2010/2011.0% category showed excellent, 60% good category, 31% good enough category, 9% less category and 0% verypoor category. It can be concluded that soccer players aged 13-15 years in SSB Se-Waterford County has agood understanding of football rules (laws of the game) 2010/2011.